A Unstructured Nodal Spectral-Element Method for the Navier-Stokes Equations (Communications in Computational Physics, 2012)
An unstructured nodal spectral-element method for the Navier-Stokes equations is developed in this paper. The method is based on a triangular and tetrahedralrational approximation and an easy-to-implement nodal basis which fully enjoys thetensorial product property. It allows arbitrary triangular and tetrahedral mesh, affording greater flexibility in handling complex domains while maintaining all essentialfeatures of the usual spectral-element method. The details of the implementation andsome numerical examples are provided to validate the efficiency and flexibility of theproposed method.